HR practices from the perspective of managers and employees in multinational enterprises in China: Alignment issues and implications - Zhu, C.; Cooper, B.; Fan, David; De Cieri, H. (Pergamon, 2013)
China's significance as a destination for foreign direct investment (FDI) is a major factor in Asia-Pacific economic growth. This paper identifies important yet unexplored matters of human resource management (HRM) in multinational enterprise (MNE) subsidiaries in China. Specifically, the study explores the alignment issues between managers and employees with respect to their knowledge of HR practices, their experience of HR practices, and their perceived effectiveness of HR practices. Both interviews and a survey covering seven MNE subsidiaries operating in China finds a lack of alignment between managers and employees in each instance, for example, in their views of intended and actual HR practices and perceived effectiveness of these practices in the areas of performance assessment, recruitment and selection and career development. The implications of the differences for managers of MNEs operating in China are identified and discussed. The limitations of the study are acknowledged and areas for further study are also suggested.